The Role Of Counseling Teacher In Smoking Behavior In Students Of SMA Negeri 1 Air Batu - Ade Ningsih, Putri; Wahyuni, Sri; Halim Nasution, Abdul (Mahir : Jurnal Ilmu Pendidikan dan Pembelajaran, 2023)
The problem in this study is the smoking behavior of SMA Negeri I Air Batu students which continues to increase every year, which in the end will cause students to experience prolonged depression and then the impact on health is so very dangerous, which can damage the heart and brain for the students. culprit. For this reason, the role of counseling guidance teachers at SMA Negeri 1 Air Batu is needed to overcome this problem where the teachers make strategies to reduce the number of smoking behavior in students, the strategy is to hold outreach by presenting resource persons at the sub-district level, namely the Puskesmas, and the Polsek, In addition to this socialization, the school also continues to conduct raids for students who use cigarettes at school and if there are students who smoke, witnesses will be charged. The results of this study indicate that: First, the role of the counseling teacher in handling smoking students is 3: (1) the counseling teacher helps students solve student problems, (2) guides students, and (3) supervises students. Second, there are 3 obstacles faced by counseling teachers in handling smoking students: (1) teachers at school do not know about counseling, (2) communication between counseling teachers and parents or guardians of students does not run smoothly, and (3) BK teachers do not have special BK hours. Third, the strategies given by the counseling teacher in handling smoking students are 3: (1) communicate with each other and create a program such as outreach, (2) provide counseling methods in the form of media leaflets. The material in the leaflet displays more pictures about the contents of cigarettes, diseases caused by smoking and ways to stop smoking. (3) provide individual counseling to students with problems.